When Salpingectomy Is Not Salpingectomy-Ipsilateral Recurrence of Tubal Pregnancy - Simona Fischer; Marc J. N. C. Keirse (Hindawi Limited, 2009)
Theoretically, total salpingectomy eliminates the risk of an ipsilateral tubal pregnancy. However, total salpingectomy is difficult to achieve using endoloops alone. We describe a situation where this resulted in an ipsilateral recurrence of tubal pregnancy which required emergency intervention and removal of the tubal remnants.